2019
DOI: 10.2106/jbjs.19.00661
|View full text |Cite
|
Sign up to set email alerts
|

Natural Language Processing for the Identification of Surgical Site Infections in Orthopaedics

Abstract: Background: The identification of surgical site infections for infection surveillance in hospitals depends on the manual abstraction of medical records and, for research purposes, depends mainly on the use of administrative or claims data. The objective of this study was to determine whether automating the abstraction process with natural language processing (NLP)-based models that analyze the free-text notes of the medical record can identify surgical site infections with predictive abilities that match the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 28 publications
(32 reference statements)
1
49
0
1
Order By: Relevance
“… 31 In orthopaedics, NLP has been applied to identify surgical site infections in free-text notes of medical records and achieved predictive abilities comparable with the manual abstraction process and superior to models that used administrative data only. 32 In hip arthroplasty, NLP has been used to identify common data elements 33 and classification of periprosthetic femur fractures. 34 Our group applied NLP to evaluate unstructured free-text patient-experience reviews of orthopaedic surgeons throughout the United States.…”
Section: Part Ii: Three Forms Of Machine Learning To Aid Clinical Decmentioning
confidence: 99%
“… 31 In orthopaedics, NLP has been applied to identify surgical site infections in free-text notes of medical records and achieved predictive abilities comparable with the manual abstraction process and superior to models that used administrative data only. 32 In hip arthroplasty, NLP has been used to identify common data elements 33 and classification of periprosthetic femur fractures. 34 Our group applied NLP to evaluate unstructured free-text patient-experience reviews of orthopaedic surgeons throughout the United States.…”
Section: Part Ii: Three Forms Of Machine Learning To Aid Clinical Decmentioning
confidence: 99%
“…26 These data are complex to use in automatization processes and will complicate widespread implementation. 27 Fourth, the determination of superficial SSIs requires a subjective interpretation of the definition, making them a difficult surveillance target both for manual and automated surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…25,[31][32][33] In addition, coding practices differ by country, and results cannot be extrapolated. Thirukumaran et al 27 investigated the use of natural language processing in detecting SSIs. Sensitivity and PPV were extremely high in the center under study; however, the performance in other centers was not investigated, and the proposed method is rather complex to implement on a large scale compared to our method.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight that NLP is far from perfect as the topics have substantial overlap. However, four categories emerged: [ 1 ] automated reporting using electronic health record (EHR) text, [ 2 ] identifying common data elements such as infection using operative reports, [ 3 ] identifying fractures from radiology reports patient, and [ 4 ] online reviews and comments after total joint arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Thirukumaran et al noted that surgical site infection (SSI) is a costly problem in hospitals and is mostly tracked through manual record review of charts or administrative and claims data. They concluded that NLP was comparable to manual chart review and significantly improved SSI detection than models using administrative data alone [ 3 ]. Karhade et al also used NLP to detect reoperation rates secondary to SSI within 90 days of lumbar discectomy at two academic and three community centers.…”
Section: Introductionmentioning
confidence: 99%